2016
DOI: 10.1097/md.0000000000004824
|View full text |Cite
|
Sign up to set email alerts
|

Different mean thickness implicates involvement of the cortex in migraine

Abstract: The results of neuroimaging studies on migraines have shown that the functions and functional connectivity networks of some brain regions are altered in migraine patients, and different brain structure volumes have also been observed in recent years. However, it is still not known whether the mean thickness of the cortex is different in migraine patients.A total of 48 migraine without aura (MWoA) patients in interictal phase and 48 healthy controls were enrolled in this study. All subjects received neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Additionally, several other regions with decreased GMV were observed, including the inferior parietal lobule and supramarginal gyrus. Alterations in the GMV of the inferior parietal lobule have been reported in many previous cerebral structural studies on migraine (Yu et al, ). Those studies showed that the cortical thickness of the inferior parietal lobe in the migraine patient group was significantly decreased compared with that in the healthy control group.…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, several other regions with decreased GMV were observed, including the inferior parietal lobule and supramarginal gyrus. Alterations in the GMV of the inferior parietal lobule have been reported in many previous cerebral structural studies on migraine (Yu et al, ). Those studies showed that the cortical thickness of the inferior parietal lobe in the migraine patient group was significantly decreased compared with that in the healthy control group.…”
Section: Discussionsupporting
confidence: 59%
“…The angular gyrus is a part of the inferior parietal lobule and is located in the posterior part of this lobule and the junction of the occipital, temporal, and parietal lobes. It is mainly involved in the response to pain and the sensation of temperature and pressure (36,37). It is also an important region in the default mode network (DMN), which participates in the brain's cognitive, emotional, behavioral and other advanced functions in the resting state (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the calcarine sulcus is responsible for multisensory processing in affective, sensory and cognitive aspects of pain [3, 30]. Furthermore, abnormal FC of the calcarine has been shown to be involved in many independent networks, corresponding to the perspective that the experience of pain is complex and involves multidimensional processing [31]. Thus, the lower activity of the left calcarine sulcus in MwoA patients could be related to the lower tolerance threshold to the normally noxious or non-noxious sensory stimuli.…”
Section: Discussionmentioning
confidence: 99%